Analysis of The Effect of Experience and Trust on The Tourism Economy After The Phenomenon of KKN DESA PENARI - Kholid Murtadlo (PT Mattawang Mediatama Solution, 2022)
The development of the tourism sector in Indonesia has increased significantly. It is due to several factors such as government policies and marketing aspects of the tourism destination managers. This study aims to analyze, test, and determine the impact of experience and trust variables on economic development, especially in the tourism economy. In this study, the tourism economy is seen in revisit intention, which impacts increasing tourist visits. The study was conducted after collecting related data and evidence. The research site is in Banyuwangi, the city where the phenomenon of KKN Desa Penari takes place. The research population and sample were the millennial generations who visited the city of Banyuwangi. The sample calculation employed was Machin's Formula. Therefore, the number of samples was found to be 147 respondents. The sampling technique utilized is accidental sampling. Furthermore, the data collection technique was by distributing online questionnaires. The results showed that Experience and Trust significantly positively affected revisit intention.